Olfactory Receptors in Semen and in the Male Tract: From Proteome to Proteins - Milardi, Domenico; Colussi, Claudia; Grande, Giuseppe; Vincenzoni, Federica; Pierconti, Francesco; Mancini, Francesca; Baroni, Silvia; Castagnola, Massimo; Marana, Riccardo; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2018)
The estimated number of testicular olfactory receptors (ORs) in mammals range between 20 and 66. Previous data reported the role of hOR17-4 and mOR23 in sperm-oocyte chemiotaxis. Proteomic analysis was performed to understand which are the ORs expressed in seminal plasma. Seminal samples by 4 fertile men were analyzed by an Ultimate 3000Nano/Micro-HPLC apparatus coupled with an LTQ-Orbitrap XL hybrid mass spectrometer. Western blot analysis confirmed the expression of 3 identified ORs. The expression of ORs in sperm cells, testis and epididymis was evaluated by confocal microscopy analysis. In seminal plasma 8 different ORs were identified by proteomics and 3 ORs have been confirmed by western blot. Confocal microscopy analysis revealed that OR4S1, OR4C13 and OR1I1 are expressed on the surface of sperm cells. In testicular tissue OR4S1 and OR1I1 are expressed in spermatocytes and spermatids and OR4C13 is expressed throughout all the tubules. In patients with spermatocyte maturation arrest OR4S1 and OR1I1 expression was reduced and a weak positivity for ORC13 was detected in the spermatogonia. OR4S1, OR4C13 and OR1I1 had intense and diffuse staining in the epididymis. This study initiated a new methodology for screening OR repertoire in sperms, testis and epididymis. Our results open new insights into OR involvement in sperm maturation and migration.